Pemberdayaan keluarga melalui home visit asuhan keperawatan gigi dan mulut di Gampong Cot Mesjid - Imran, Herry; Niakurniawati, Niakurniawati; Nasri, Nasri; Ratna, Ratna; Wilis, Ratna; Keumala, Cut Ratna; Andriani, Andriani (Jurnal PADE: Pengabdian & Edukasi, 2024)
Family empowerment through Home Visits, family dental and oral health care is an effective approach to improve the quality of a person's health through improving dental health.  Family dental nursing care (home visit service) with a pick-up strategy provides motivation for the willingness or will to carry out activities in the positive direction of family dental health actions. This community service is carried out by a descriptive method, with the target of children and their parents as respondents. Data analysis uses univariate analysis using the Intervention T test provided in the form of problem-based counseling, measuring the status of children's dental health and demonstrating how to brush their teeth. The results of community service are the improvement of knowledge, attitudes and actions of mothers and changes in children's dental health status (pre-test, post test I, post test II) in family empowerment through home visits for dental and oral nursing care in improving dental health status in Gampong Cot Mosque, Lueng Bata Banda Aceh District.It is hoped that the Puskesmas can make the UKGM program using a family empowerment pattern through home visits, dental and oral nursing care through home visit services in improving the degree of dental and oral health of families.